Effects of Subduction Fluids and Fractional Crystallization on the Magnetic Minerals Formation in the Back‐Arc Basin - Jie Xu; Zhaoxia Jiang; Xia Zhang; Sangzhong Li; Xiyao Li; Long Chen; Haonan Song; Yuying Chen; Yuzhen Zhang; Zehua Guo; Kun Guo; Qingsong Liu (Geophysical Research Letters)
Abstract (Titano)magnetite is the major magnetic carrier in igneous rocks, whether it can decode the influence of subduction fluids and fractional crystallization characteristics in back‐arc basins is unclear. Here, we performed petrographic and magnetic analyses on volcanic samples from the Okinawa Trough, with titanomagnetite as the dominant magnetic mineral. Results show that the Curie temperature of Ti‐rich titanomagnetites (Tc TM‐R) not only has the potential to identify the influence of subduction fluids in back‐arc basins but also can be used to differentiate basalts and basaltic andesites that have been formed in different geologic settings. Additionally, the magnetic domain state ranges from single domain to multi‐domain as the fractional crystallization proceeds. Our study illustrates that magnetic properties of titanomagnetite are potential tracers for subduction fluids and fractional crystallization, which is of referential significance for research on relatively scarce samples from subduction zones and even extraterrestrial bodies.